Inhibition of WEE1 Suppresses the Tumor Growth in Laryngeal Squamous Cell Carcinoma - Yuan, Meng-Ling; Li, Pei; Xing, Zi-Hao; Di, Jin-Ming; Liu, Hui; Yang, An-Kui; Lin, Xi-Jun; Jiang, Qi-Wei; Yang, Yang; Huang, Jia-Rong; Wang, Kun; Wei, Meng-Ning; et al. (Frontiers in Pharmacology, 2018)
WEE1 is a tyrosine kinase that regulates G2/M cell cycle checkpoint and frequently overexpressed in various tumors. However, the expression and clinical significance of WEE1 in human laryngeal squamous cell carcinoma (LSCC) are still unknown. In this study, we found that WEE1 was highly expressed in LSCC tissues compared with adjacent normal tissues. Importantly, overexpression of WEE1 was correlated with T stages, lymph node metastasis, clinical stages and poor prognosis of LSCC patients. Furthermore, inhibition of WEE1 by MK-1775 induced cell growth inhibition, cell cycle arrest and apoptosis with the increased intracellular reactive oxygen species (ROS) levels in LSCC cells. Pretreatment with ROS scavenger N-acetyl-L-cysteine could reverse MK-1775-induced ROS accumulation and cell apoptosis in LSCC cells. MK-1775 also inhibited the growth of LSCC xenografts in nude mice. Altogether, these findings suggest that WEE1 is a potential therapeutic target in LSCC, and inhibition of WEE1 is the prospective strategy for LSCC therapy.